Reconstruction of Creditor Rights: A Juridical Analysis of the Implications of Non-Registration of Fiduciary Guarantees on Preferential Rights and Execution of Collateral - Puguh Triwibowo (Journal of Social Research, 2026)
Law Number 42 of 1999 concerning Fiduciary Guarantee asserts that registration constitutes a constitutive element for the establishment of rights in rem (zakelijk). However, a disparity between legal norms (das sollen) and empirical practices (das sein) remains evident, characterized by the prevalence of creditors neglecting the registration obligation for the sake of cost efficiency. This study aims to dissect the juridical consequences of such negligence, particularly regarding the degradation of creditor status from separatist to concurrent, as well as the forfeiture of the privilege of preference rights. Utilizing a normative juridical research method with statutory and conceptual approaches, this study concludes that an unregistered fiduciary guarantee deed merely generates an obligatory relationship (personal agreement). The fatal implications include the loss of executorial title (parate executie), the absence of legal standing in non-litigation execution, and the extinguishment of droit de suite protection against third parties. The synergy between the role of Notaries in providing legal counseling and the firmness of the Ministry of Law in administration serves as the key to mitigating these risks.